An innovative in vitro device providing continuous low doses of γ-rays mimicking exposure to the space environment: A dosimetric study. (February 2018) - Pereda-Loth, V.; Franceries, X.; Afonso, A.S.; Ayala, A.; Eche, B.; Ginibrière, D.; Gauquelin-Koch, G.; Bardiès, M.; Lacoste-Collin, L.; Courtade-Saïdi, M.
Abstract: Astronauts are exposed to microgravity and chronic irradiation but experimental conditions combining these two factors are difficult to reproduce on earth. We have created an experimental device able to combine chronic irradiation and altered gravity that may be used for cell cultures or plant models in a ground based facility. Irradiation was provided by thorium nitrate powder, conditioned so as to constitute a sealed source that could be placed in an incubator. Cell plates or plant seedlings could be placed in direct contact with the source or at various distances above it. Moreover, a random positioning machine (RPM) could be positioned on the source to simulate microgravity. The activity of the source was established using the Bateman formula. The spectrum of the source, calculated according to the natural decrease of radioactivity and the gamma spectrometry, showed very good adequacy. The experimental fluence was close to the theoretical fluence evaluation, attesting its uniform distribution. A Monte Carlo model of the irradiation device was processed by GATE code. Dosimetry was performed with radiophotoluminescent dosimeters exposed for one month at different locations (x and y axes) in various cell culture conditions. Using the RPM placed on the source, we reached a mean absorbed dose of gamma rays of (0.33 ± 0.17) mSv per day. In conclusion, we have elaborated an innovative device allowing chronic radiation exposure to be combined with altered gravity. Given the limited access to the International Space Station, this device could be useful to researchers interested in the field of space biology.